The Analysis of Ecotourism Eligibility in the North Coast of Makassar - Akram, Andi Muhammad; Leksono, Amin Setyo; Afandhi, Aminuddin; Yunus, Muhammad; Risman, Risman (Journal of Indonesian Tourism and Development Studies, 2018)
Ecotourism is one of environmentally friendly tourism activities which prioritizes the aspects of nature conservation, social economic culture empowerment and aspects of learning and education. Bira village, located in the coast of Makassar, has a good mangrove potential and it can be developed as a place of mangrove ecotourism. This research aimed to analyze the potential of ecology, socio-economic and supporting infrastructure for the eligibility of developing Mangrove ecotourism at Bira village of Makassar. The research design used was survey research which was descriptive analysis through case study approach. The method used was quantitative and qualitative approach. Quantitative approach used questionnaire method while qualitative approach used in-depth interview technique and field observation. Data obtained was analyzed by weighting method, spatial analysis and AHP. The results showed that the criteria of ecological eligibility included in the category was the value of 73.99; the category of socioeconomic eligibility was in accordance with the value of 81.55 and the eligibility criteria of supporting infrastructure included in the category in accordance with the acquisition value was 77.93.Keywords: ecotourism, eligibility criteria, mangrove.